PENGARUH GINI RASIO, RATA-RATA LAMA SEKOLAH DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PERSENTASE PENDUDUK MISKIN DI KABUPATEN/KOTA JAWA TIMUR TAHUN 2023 - Irpani, Khoirul; Revana, Sethela Adhelia; Futri, Adellia; Tisyafianto, Muhammad Rafi Rizqulloh; Pradua, Raihan Septa (Buletin Ekonomika Pembangunan, 2025)
Poverty is still a major problem in East Java because the number remains high despite various countermeasures programs that have been implemented by the government. This study aims to analyze the influence of Gini Ratio, Average School Length (RLS), and Open Unemployment Rate (TPT) on the percentage of poor people in East Java districts/cities in 2023. The novelty of this study lies in the integration of these three variables in one current empirical model so as to provide a comprehensive picture of the structural factors that affect poverty at the regional level. The contribution of the research is present through the provision of empirical evidence that fills the gap in the literature regarding the simultaneous relationship between income inequality, education, and unemployment in explaining poverty. The study used a descriptive quantitative approach based on secondary data analyzed through multiple linear regression with the help of SPSS software. The results of the study showed that the three independent variables had a significant effect on the poverty rate. Partially, Gini Ratio and RLS have a negative and significant effect, while TPT has a negative but not significant effect. These findings affirm the importance of income equity, improving the quality of education, and strengthening productive economic access as a poverty reduction strategy. Therefore, regional development policies should be focused on increasing access to education, economic empowerment of low-income communities, and creating productive jobs. Keywords: Gini Ratio, Average School Length, Open Unemployment Rate, Poverty, East Java.